Infektivitas parasit Ichtyophthirius multifiliis yang disimpan pada suhu rendah - Rahman, ,; Sukenda, ,; Nuryati, Sri; Hidayatullah, Dendi (Jurnal Akuakultur Indonesia, 2016)
ABSTRACT The aim of this study was to evaluate infectivity of Ichtyophthirius multifiliis which caused white spot disease maintained at low temperature without its host. Briefly, the trophont stage of parasites were subjected at control (28 °C) and lower temperature (9 °C) for 14 consecutive days of observation. The rate of survival, and excystment of descendants were examined descriptively at the last day of observation. Here, the infectivity of parasite then performed by means infecting the model fish Poecilia sphenops (black moly) with escaping theronts. The results revealed that the survival rate and excystment  rate of parasite were decreased as maintaining period increased. The final rate of survival, and excystment of parasite were 35% and 33,3% respectively. Additionally, the descendants came out with high abnormality which recognized by weak mobility and lower infectivity (50%) compared to the control (80%). Then, it is concluded that, maintaining I. multifiliis at low temperature without its host for 14 consecutive days will decreased the infectivity. Keywords: white spot, obligat parasite, excystment, infectivity  ABSTRAK Penelitian ini bertujuan untuk mengevaluasi infektivitas parasit Ichtyophthirius multifiliis penyebab penyakit bintik putih (white spot) yang dipelihara tanpa inang pada suhu rendah. Parasit dengan stadia trophont dipelihara pada suhu ruang (28 °C) dan suhu rendah (9 °C) selama 14 hari. Selama masa pemeliharaan tersebut tingkat kelulusan hidup, dan tingkat eksismen parasit diukur dan dibandingkan secara deskriptif. Hari terakhir pemeliharaan dilakukan uji tantang pada ikan black moly Poecilia sphenops untuk menilai infektivitas parasit. Hasil penelitian memperlihatkan bahwa tingkat kelulusan hidup dan eksismen parasit semakin menurun dengan bertambahnya masa pemeliharaan. Akhir pengamatan  kelangsungan hidup, dan nilai eksismen tersebut berturut-turut adalah 35% dan 33%. Parasit yang disimpan pada suhu rendah selama 14 hari memperlihatkan infektivitas yang lebih rendah (50%) dibandingkan dengan perlakuan kontrol (80%). Kesimpulannya, penyimpanan parasit I. multifiliis pada suhu rendah selama 14 hari dapat menurunkan infektivitas parasit pada inang. Kata kunci: bintik putih, parasit obligat, eksismen, infektivitas